2019
DOI: 10.3892/or.2019.6987
|View full text |Cite
|
Sign up to set email alerts
|

SPAG9/MKK3/p38 axis is a novel therapeutic target for liver cancer

Abstract: Sperm-associated antigen 9 (SPAG9) is a biomarker and potential therapeutic target for several cancers; however, its involvement in liver cancer progression is not clear. The aim of the present study was to determine whether SPAG9 regulates proliferation of liver cancer. Immunohistochemistry and cell immunofluorescence were used to confirm the expression and the localization of SPAG9 in human liver cancer tissues and the liver cancer-derived HepG2 cells. A small interfering RNA (siRNA) designed to target SPAG9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Certainly, the MKK3/p38 axis has been increasingly studied in cancer. Studies have shown that the MKK3/p38 axis regulates cell proliferation, apoptosis, and cell cycle progression in hepatoma cells 27 . Furthermore, we have demonstrated that linc02381 was upregulated in RA tissues and RA cell line, and linc02381 activated MAPK signal pathway by absorbing miR-590-5p to promote RA-FLS proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the MKK3/p38 axis has been increasingly studied in cancer. Studies have shown that the MKK3/p38 axis regulates cell proliferation, apoptosis, and cell cycle progression in hepatoma cells 27 . Furthermore, we have demonstrated that linc02381 was upregulated in RA tissues and RA cell line, and linc02381 activated MAPK signal pathway by absorbing miR-590-5p to promote RA-FLS proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of p38-activation may promote tumor growth in cancers with a decreased level of MKK3 [57,75], suggesting its tumor-suppressive function. On the other hand, the oncogenic role for MKK3 has been reported in multiple tumor types, including melanoma, colorectal, liver, esophageal, cervical, and breast cancers [51,52,[76][77][78][79][80]. Analysis of genomics data shows that MKK3 is either up-or downregulated in different cancer types and different groups of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…47 Currently, newly discovered molecular markers related to liver cancer include SPAG9/MKK3/p38 axis, AKR1C3, B3GAT3, DYRK2 and BPTF. [48][49][50][51][52] The study showed that down-regulation of Sperm-associated antigen 9 (SPAG9) can reduce the expression of MKK3 and p38 proteins, inhibits cell proliferation and promotes cell apoptosis. Therefore, SPAG9 may be a potential new target for liver cancer treatment.…”
Section: Liver Cancer Related Somatic Mutationsmentioning
confidence: 99%
“…Therefore, SPAG9 may be a potential new target for liver cancer treatment. 48 In addition, it was found that AKR1C3 is an independent biomarker for the prognosis of liver cancer by database mining. However, the expression level of AKR1C3 was inversely correlated with the overall survival of liver cancer patients.…”
Section: Liver Cancer Related Somatic Mutationsmentioning
confidence: 99%